Implementation of 5-DOF Robot Arm Control with Inverse Kinematics Through Interactive GUI - Ryan Satria Wijaya; Muhamad Ilham; Eko Rudiawan Jamzuri; Anugerah Wibisana; Rifky Afriza; Emelia Rosari Siregar; Senanjung Prayoga (Politeknik Negeri Batam, 2026)
This work presents a control system for a five-joint (5-DOF) robotic arm designed for educational use, combining geometric inverse kinematics with a custom Python graphical interface. Instead of relying on iterative approaches, a closed-form inverse kinematics formulation is implemented to directly derive joint configurations from Cartesian coordinates. System functionality is supported through communication between a host computer and an ESP32 microcontroller via UART serial interface, enabling real-time control, workspace verification, and kinematic validation using forward kinematics. For simplicity in operation, the wrist orientation is kept fixed so that the control system focuses primarily on positional accuracy. experimental results show an average IK computation time of 1,7 ms, a mean positioning error of 2,46 mm, and a peak deviation of 4,91 mm across representative workspace targets. The obtained results confirm that the system achieves stable and reliable performance suitable for low-cost laboratory experimentation and educational robotics applications.